THE DEVELOPMENT OF E-COMMERCE CAPABILITY AND ITS IMPACT ON BUSINESS PERFORMANCE: A CASE OF MALAYSIAN MANUFACTURING INDUSTRIES - MUHAMMAD JEHANGIR, MUHAMMAD JEHANGIR (2012)
Firms around the world are embracing electronic-commerce (EC) technologies as strategic marketing tools to enhance the competitive advantage and organizational performance. Over the last two decades, EC obtained prominent importance and has become a key dimension to a firm value. Many firms have invested in this technology to compete in the fast paced business environment. However, the literature contains mixed findings of EC on overall business performance and the success of EC implementations is scarce in the literature. This study attempts to investigate why some firms are getting advantages from EC while some are not. By examining the attributes of firm’s business, human and IT resources, this research seeks to enhance an understanding of the relationship between EC capability and business performance. A total of 287 participants from manufacturing companies throughout Malaysia completed 63 items survey instrument. The instrument measured business resources, human resources, IT resources and business performance factors. Reliability and factor analysis were assessed for data screening; estimation of construct validity by confirmatory factor analysis (CFA) and the relationships between factors were established with structural equation modelling (SEM). The results of descriptive statistics and reliability presented data usability for current study and by examining firm’s business, human and IT resources the results of SEM provided the evidence of significant relationship between EC capability and business performance. This strongly suggests the necessary investments for the utilization of firm’s resources for the implementation and usage of EC technologies. The significant relationship between EC capability and business performance also provides a base to explain that EC is not only a technology; but also a complete business process needing proper strategies to gain its value. The results of this study may explain the issue of mixed business benefits from the implementation of EC technologies. Finally this investigation offers new insights that applicable to the development of EC capability and its returns. In so doing, this study may help theorists and practitioners, especially within the manufacturing industries, to develop EC strategies at post- and pre- implementation levels of EC application. This study is helpful in providing the resource-based and dynamic capability perspectives of EC in terms of better understanding and usage of the resources for the implementation of EC technology. The findings of this study can be taken into consideration for the successful usage of EC. Index terms: electronic-commerce, capability, resources, implementation, manufacturing industries